2023
DOI: 10.1080/22221751.2023.2281356
|View full text |Cite
|
Sign up to set email alerts
|

Experimental co-infection of calves with SARS-CoV-2 Delta and Omicron variants of concern

Konner Cool,
Natasha N. Gaudreault,
Jessie D. Trujillo
et al.

Abstract: Since emerging in late 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has repeatedly crossed the species barrier with natural infections reported in various domestic and wild animal species. The emergence and global spread of SARS-CoV-2 variants of concern (VOCs) has expanded the range of susceptible host species. Previous experimental infection studies in cattle using Wuhan-like SARS-CoV-2 isolates suggested that cattle were not likely amplifying hosts for SARS-CoV-2. However, SARS-CoV-2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Earlier studies suggested cattle are poorly permissive to infection with SARS-CoV-2[11,12]. Further, a recent study suggested that cattle are more permissive to infection with SARS-CoV-2 Delta than Omicron BA.2[18]. Further, the study also found limited seroconversion and no clear evidence of transmission to sentinel calves[18].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Earlier studies suggested cattle are poorly permissive to infection with SARS-CoV-2[11,12]. Further, a recent study suggested that cattle are more permissive to infection with SARS-CoV-2 Delta than Omicron BA.2[18]. Further, the study also found limited seroconversion and no clear evidence of transmission to sentinel calves[18].…”
Section: Discussionmentioning
confidence: 93%
“…Further, a recent study suggested that cattle are more permissive to infection with SARS-CoV-2 Delta than Omicron BA.2[18]. Further, the study also found limited seroconversion and no clear evidence of transmission to sentinel calves[18]. Serological studies from Italy[19] and Germany[20] reported antibody evidence of natural SARS-CoV-2 exposure of cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations